Performance Comparison of Different Exhaust Exchanger Types Considering Peak Net Power and Optimal Dimension in a Thermoelectric Generator System. Issue 4 (12th April 2018) - He, Wei; Wang, Shixue
Abstract: This study introduces a more scientific comparison method to obtain an effective exhaust heat exchanger in a thermoelectric generator (TEG) system when recycling the waste heat from an engine exhaust, and evaluate the performance of different kinds of exhaust heat exchangers. Moreover, the effect of the heat transfer and fluid flow characteristics on the thermoelectric performance and the dimensional optimization characteristics are analyzed. A complete numerical TEG model using the finite element method is formulated with three common plate‐type exhaust heat exchangers (i.e., smooth, offset‐strip fin, and corrugated louvered fin types) taken as examples. The results show that it is more scientific and recommended to evaluate the heat exchanger performance by comparing its maximum net power with its separate optimal heat exchange size taken for different heat exchanger types. In this study, the corrugated louvered fin type has obvious advantages. The dimensional optimization results for different heat exchanger types are also presented herein. The method used and the results obtained provide guidance in achieving an efficient exhaust heat exchanger. Abstract : A more scientific comparison method to select an effective exhaust heat exchanger among different types in thermoelectric generator systems is introduced by numerical simulation with three common exchangers taken as examples. The thermoelectric performance and dimensional optimization characteristics are analyzed for each type. The method used and the results obtained provide guidance in achieving highly efficient exhaust heat exchanger design.